If it's not what You are looking for type in the equation solver your own equation and let us solve it.
(2x-20)=(x-15)
We move all terms to the left:
(2x-20)-((x-15))=0
We get rid of parentheses
2x-((x-15))-20=0
We calculate terms in parentheses: -((x-15)), so:We get rid of parentheses
(x-15)
We get rid of parentheses
x-15
Back to the equation:
-(x-15)
2x-x+15-20=0
We add all the numbers together, and all the variables
x-5=0
We move all terms containing x to the left, all other terms to the right
x=5
| 4x+8+6x−5=33 | | 3(1-8x)-6=93 | | 2x-20=x-15 | | 3=t+11.5−t | | 18x=10x+2 | | 30x+12x=5x-19 | | 8(8m-2)-8m=0 | | -3(1-8n)=123 | | 1.4x=8+x | | 12/11=p/12p= | | (H+4)=6h+4 | | 7r-3=3r+4r-3 | | 8n-(5n+)=14 | | R=7/3p+40 | | 39=-2x-13 | | y/5+y/2=4/5 | | 39=-2x-14 | | -5(6-3x)=4(6+6x) | | 13=5m-2* | | -5=14-x | | -5(5x+3)-5x+1=−44 | | 4x2–48x=0 | | 1/3v=25 | | 39=u | | -(4+2w)=6w | | -14=a.18 | | 3=p.13 | | –4t−8=–t+4 | | n/2-7=-4.02 | | -6(-2x-9)x1=9x+50 | | –7−8y=–9y | | 5(3x-1)=25(x+1) |